KONSEP KEPEMIMPINAN PERSPEKTIF TASAWUF POSITIF MODERN - Ahmad Buchori Muslim (STAI Ma'had Aly Al-Hikam Malang, 2019)
Sufism as the core of Islamic teachings emerged by providing solutions and therapies for human problems by bringing closer to Allah the Creator. However, Sufism has been perceived as an inner practice that detaches itself from the world. However, lately, there is an understanding of Sufism which does not make its practitioners withdraw from the environment and instead requires its practitioners to go down to the community and contribute to solving problems faced by their communities. Sufism is known as